Local economic development in Alexandra: A case study of woman in the informal sector - Moyo, Anele (My University, 2006)
This research report covers the progress of local economic development in Alexandra under the Alexandra Renewal Project and what the government has done (or is doing) to assist women street traders. It begins by looking back at the history of development in Alexandra, followed by an overview of Urban Renewal Programme which guides the Alexandra Renewal Project whose LED components forms a crucial part of this report. The report reviews the literature on the informal sector and the policy that guides the development and promotion of the sector in South Africa. After reviewing literature on the informal sector, the report turns to local economic development literature, arguing for a more ‘developmental” role that the government should take towards LED initiatives in the country. The research findings that follow provide my opinions and those of different stakeholders involved in the LED initiatives and those that are affected by the initiatives, mainly women street traders in Alexandra.
Faculty of Humaninties And Social Sciences School of Social Sciences 0003962g anele30@hotmail.com
Keywords: Local; Economic; Development; Informal Sector; Alexandra